2019
DOI: 10.1590/0103-8478cr20180587
|View full text |Cite
|
Sign up to set email alerts
|

Lipid content and fatty acids compositions in commercial cuts of young goat meat

Abstract: Brazil has the largest herd of goats of the American continent, with more than 9 million head. Goat farming is considered a growing and important activity for the economy, mainly in the northeastern region of Brazil .In this research, were determined the lipid content and the composition of fillet and shank fatty acids of young goats, registered in the inspection sector of the Ministry of Agriculture and marketed in the city of Salvador (Bahia). The average percentage of total lipids in the fillet was 1.68±0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Among all fatty acids, all cuts had oleic acid (C18:1n9), palmitic acid (C16:0), and stearic acid (C18:0) as major fatty acids. The results were correlated with some previous research that reported that these three fatty acids were the major fatty acids found in fillet and shank goat cuts [10], as well as loin, hind leg, neck, or either foreleg [9]. From the nutrition aspect, the PUFA/SFA ratio can be used as an index for determining if the nutritive quality should be high.…”
Section: Fatty Acid Profilessupporting
confidence: 86%
See 2 more Smart Citations
“…Among all fatty acids, all cuts had oleic acid (C18:1n9), palmitic acid (C16:0), and stearic acid (C18:0) as major fatty acids. The results were correlated with some previous research that reported that these three fatty acids were the major fatty acids found in fillet and shank goat cuts [10], as well as loin, hind leg, neck, or either foreleg [9]. From the nutrition aspect, the PUFA/SFA ratio can be used as an index for determining if the nutritive quality should be high.…”
Section: Fatty Acid Profilessupporting
confidence: 86%
“…Compared with all cuts, SFA and UFA were highest in the rib and hind leg, respectively (p < 0.05). Differences in the total fat content and fatty acid composition between fillet and shank goat cuts have been noted [10]. The fillet and shank cuts contained an average of 1.68 and 4.02% fat, respectively, with a total SFA and PUFA content ranging from 42.75 to 45.23% and 12.35 to 14.04% for the fillet and shank cuts, respectively.…”
Section: Fatty Acid Profilesmentioning
confidence: 95%
See 1 more Smart Citation